Opposing profiles of Netrin-1 and adiponectin in metabolic inflammation and insulin resistance - Ramos-Zavala, María Guadalupe; García-Galindo, Jesús Jonathan; Beltrán-Ramírez, Alberto; Balleza-Alejandri, Luis Ricardo; Peña-Durán, Emiliano; Huerta-Huerta, Alfredo; Rubio-Arellano, Edy David; López-Murillo, Luis Daniel; Pascoe-Gonzalez, Sara; Campos-Bayardo, Tannia Isabel; Suárez-Rico, Daniel Osmar (Frontiers in Pharmacology, 2025)
IntroductionObesity-driven low-grade inflammation contributes to insulin resistance (IR) and metabolic dysfunction. Beyond its axon-guidance role, Netrin-1 promotes macrophage retention in inflamed adipose tissue, whereas adiponectin exerts anti-inflammatory, insulin-sensitizing effects. We aimed to compare serum Netrin-1, interleukin-6 (IL-6), high-sensitivity C-reactive protein (hs-CRP), and adiponectin across metabolic profiles and assess their associations with systemic inflammation.MethodsWe conducted an analytical cross-sectional study in adults (n = 60): metabolically healthy controls (C, n = 20), preclinical obesity (PO; HOMA‐IR < 2.5, n = 20), and clinical obesity with insulin resistance (CO; HOMA-IR>2.5, n = 20). Anthropometrics, fasting glucose/insulin, lipid profile, and serum biomarkers were obtained; group differences and correlations were analyzed (non-parametric tests where appropriate).ResultsBetween-group testing showed higher Netrin‐1 in CO versus controls (Kruskal–Wallis p = 0.013; C < CO), with no significant difference versus PO. IL-6 was elevated in both PO and CO versus controls (Kruskal–Wallis p < 0.001). hs-CRP peaked in PO versus both C and CO (Kruskal–Wallis p < 0.001). Adiponectin was lower in CO and inversely correlated with hs-CRP (r = –0.22) and IL‐6 (r = –0.53, p < 0.001).DiscussionCirculating Netrin-1 and adiponectin display opposing profiles aligned with pro- versus anti-inflammatory signaling in metabolic dysfunction. These findings support the Netrin–1/adiponectin axis as an immunometabolic marker set in early IR states. The cross-sectional design limits causal inference; longitudinal studies integrating tissue-level measurements are warranted.